2016
DOI: 10.1073/pnas.1605085113
|View full text |Cite
|
Sign up to set email alerts
|

Syntax compensates for poor binding sites to encode tissue specificity of developmental enhancers

Abstract: Transcriptional enhancers are short segments of DNA that switch genes on and off in response to a variety of intrinsic and extrinsic signals. Despite the discovery of the first enhancer more than 30 y ago, the relationship between primary DNA sequence and enhancer activity remains obscure. In particular, the importance of "syntax" (the order, orientation, and spacing of binding sites) is unclear. A high-throughput screen identified synthetic notochord enhancers that are activated by the combination of ZicL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
162
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 153 publications
(176 citation statements)
references
References 30 publications
13
162
1
Order By: Relevance
“…A second study has shown that an enhancer of the Drosophila Suppressor of Hairless gene is composed of overlapping elements termed submodules that can function independently to activate enhancer activity (Liu & Posakony, 2014). In addition, a recent study of a notochord enhancer structure in Ciona points to the importance of TF binding site affinity and arrangement in conferring tissue specificity on enhancer function (Farley, Olson, Zhang, Rokhsar, & Levine, 2016; reviewed by Barolo, 2016; Crocker, Noon, & Stern, 2016). The presence of repeat sequence motifs in these enhancers, and their conserved positioning, points to the necessity of considering binding site position and TF avidity (Levo & Segal, 2014; Sayal, Dresch, Pushel, Taylor, & Arnosti, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A second study has shown that an enhancer of the Drosophila Suppressor of Hairless gene is composed of overlapping elements termed submodules that can function independently to activate enhancer activity (Liu & Posakony, 2014). In addition, a recent study of a notochord enhancer structure in Ciona points to the importance of TF binding site affinity and arrangement in conferring tissue specificity on enhancer function (Farley, Olson, Zhang, Rokhsar, & Levine, 2016; reviewed by Barolo, 2016; Crocker, Noon, & Stern, 2016). The presence of repeat sequence motifs in these enhancers, and their conserved positioning, points to the necessity of considering binding site position and TF avidity (Levo & Segal, 2014; Sayal, Dresch, Pushel, Taylor, & Arnosti, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the affinity with which a TF binds to its DNA site, which is controlled, in part, by the particular sequence of that binding motif, is increasingly recognized as a crucial factor in both the quantitative and qualitative control of gene expression (8)(9)(10)(11)(12)(13)(14)(15)(16). In PNAS, Farley et al (17) investigate how the binding affinity and the spatial arrangement of TF binding sites within enhancers interact to encode precise patterns of gene expression in developing embryos.…”
mentioning
confidence: 99%
“…Within the wild-type Otx-a enhancer, certain ETS and GATA sites have relatively poor predicted binding affinity but optimal pairwise spacing, whereas other sites have higher affinity but suboptimal spacing (14). The discovery of a synthetic Otx-a variant with ectopic notochord activity, and comparisons against other synthetic modules with slightly different compositions, suggest that similar trade-offs can modulate gene expression in the notochord (17). This observation led Farley et al (17) to ask an intriguing question: Can we use what we have learned about constraints on TF binding site identity, affinity, and arrangement to find new notochord enhancers in the Ciona genome, using sequence data alone?…”
mentioning
confidence: 99%
See 2 more Smart Citations